Arsenic and mercury tolerant rhizobacteria that can improve phytoremediation of heavy metal contaminated soils - Daniel Rojas-Solis; John Larsen; Roberto Lindig-Cisneros (PeerJ, 2023)
Background Mining deposits often contain high levels of toxic elements such as mercury (Hg) and arsenic (As) representing strong environmental hazards. The purpose of this study was the isolation for plant growth promoting bacteria (PGPBs) that can improve phytoremediation of such mine waste deposits. Methods We isolated native soil bacteria from the rhizosphere of plants of mine waste deposits and agricultural land that was previously mine tailings from Tlalpujahua Michoacán, Mexico, and were identified by their fatty acid profile according to the MIDI Sherlock system. Plant growth promoting traits of all bacterial isolates were examined including production of 3-indoleacetic acid (IAA), siderophores, biofilm formation, and phosphate solubilization. Finally, the response of selected bacteria to mercury and arsenic was examined an in-vitro assay. Results A total 99 bacterial strains were isolated and 48 identified, representing 34 species belonging to 23 genera. Sixty six percent of the isolates produced IAA of which Pseudomonas fluorescens TL97 produced the most. Herbaspirillum huttiense TL36 performed best in terms of phosphate solubilization and production of siderophores. In terms of biofilm formation, Bacillus atrophaeus TL76 was the best. Discussion Most of the bacteria isolates showed high level of tolerance to the arsenic (as HAsNa2O4 and AsNaO2), whereas most isolates were susceptible to HgCl2. Three of the selected bacteria with PGP traits Herbispirillum huttiense TL36, Klebsiella oxytoca TL49 and Rhizobium radiobacter TL52 were also tolerant to high concentrations of mercury chloride, this might could be used for restoring or phytoremediating the adverse environmental conditions present in mine waste deposits.